Molecular modeling of peroxidase and polyphenol Oxidase: Substrate specificity and active site comparison - Prontipa Nokthai (2018)
Peroxidases (POD) and polyphenol oxidase (PPO) are enzymes that are well known to be involved in the enzymatic browning reaction of fruits and vegetables with different catalytic mechanisms. Both enzymes have some common substrates, but each also has its specific substrates. In our computational study, the amino acid sequence of grape peroxidase (ABX) was used for the construction of models employing homology modeling method based on the X-ray structure of cytosolic ascorbate peroxidase from pea (PDB ID:1APX), whereas the model of grape polyphenol oxidase was obtained directly from the available X-ray structure (PDB ID:2P3X). Molecular docking of common substrates of these two enzymes was subsequently studied. It was found that epicatechin and catechin exhibited high affinity with both enzymes, even though POD and PPO have different binding pockets regarding the size and the key amino acids involved in binding. Predicted binding modes of substrates with both enzymes were also compared. The calculated docking interaction energy of trihydroxybenzoic acid related compounds shows high affinity, suggesting specificity and potential use as common inhibitor to grape ascorbate peroxidase and polyphenol oxidase. © 2010 by the authors; licensee MDPI, Basel, Switzerland.